Symbol. - Hyland, Angus; Bateman, Steven (London : King, 2011)
1. Abstract : Circles : Transport for London; CND (Campaign for Nuclear Disarmament) ; Squares and rectangles : Deutsche Bank ; Triangles : MOT; Paul Forrer AG ; Polygons ; Ovals and ovoids ; Geometric combinations ; Rhombi ; Cubes and 3-D forms : BAM (Royal BAM Group nv); The Cooper Union; Museum für Gegenwartskunst Siegen ; Strips ; Plaid, woven and chequered motifs ; Chevrons ; Diamonds ; Wavy lines, ribbons and zigzags ; Dots ; Rings and roundels ; Loops, knots and guilloche ; Curves, crescents and arcs : Continental Airlines; Nike ; Radiating (circular) : Munich Olympics 1972 ; Rotary (Circular) ; Amorphous ; Crosses ; Arrows : Swiss Federal Railway (SBB CFF FFS); British Rail ; Speech bubbles and punctuation ## ##2. Representational : Water, liquid and waves ; Snowflake ; Fire and flames ; Flowers ; Plants and leaves : RACE (Research for an Alternative and Clean Energy) ; Trees ; Fruits and vegetables : Apple ; Domesticated animals ; Wild animals : WWF; The New York Public Library ; Birds : Sprint; Penguin; BOAC (British Overseas Airways Corporation) ; Insects ; Extinct and mythical creatures ; Landscapes ; Stars ; The sun ; Planets, globes and moons : Pan Am ; Figures ; Faces ; Eyes : CBS (Columbia Broadcasting System) ; Hands and feet ; Architecture : Nouveau Théâtre de Montreuil; Centre Georges Pompidou ; Transport ; Tools, machinery and appliances ; Everyday objects ; Sports ; Music, craft, art and fashion ; Food and drink ; Books and paper ; Hearts ; Crowns : KLM ; Heraldry, shields and flags ; Locks and keys.
boek